2014
DOI: 10.1186/preaccept-1743653389136389
|View full text |Cite
|
Sign up to set email alerts
|

Axonal degeneration in multiple sclerosis: can we predict and prevent permanent disability?

Abstract: Axonal degeneration is a major determinant of permanent neurological impairment during multiple sclerosis (MS). Due to the variable course of clinical disease and the heterogeneity of MS lesions, the mechanisms governing axonal degeneration may differ between disease stages. While the etiology of MS remains elusive, there now exist potential prognostic biomarkers that can predict the conversion to clinically definite MS. Specialized imaging techniques identifying axonal injury and drop-out are becoming establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 89 publications
(119 reference statements)
0
19
0
Order By: Relevance
“…Quantitative analysis of g-ratios (the inner axonal diameter to the total outer diameter) confirmed that mutant Htt significantly increased this ratio in PLP-150Q mice in an age-dependent manner (Figure 5C). It is well known that demyelination can lead to axonal degeneration (Rodriguez and Scheithauer, 1994; Sathornsumetee et al, 2000; Lee et al, 2014). Consistently, electron microscopy also revealed a number of degenerated axons, which appear swollen and dark, in PLP-150Q mice at 5 months of age (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative analysis of g-ratios (the inner axonal diameter to the total outer diameter) confirmed that mutant Htt significantly increased this ratio in PLP-150Q mice in an age-dependent manner (Figure 5C). It is well known that demyelination can lead to axonal degeneration (Rodriguez and Scheithauer, 1994; Sathornsumetee et al, 2000; Lee et al, 2014). Consistently, electron microscopy also revealed a number of degenerated axons, which appear swollen and dark, in PLP-150Q mice at 5 months of age (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the original research focus defining the autoimmune mechanisms that are operative in multiple sclerosis (MS) and the therapeutic developments that have achieved substantive reductions in relapse rates, axonal degeneration and neural tissue injury still remain the arbiter of profound neurological deficit in individuals living with this severe disease (for review, see Lee et al, 2014). Two models of axonopathy/demyelination have been suggested in MS pathology; primary axonal degeneration or oligodendrocyte dystrophy followed by demyelination (inside-out), or demyelination leading to secondary axonal degeneration (outside-in; Trapp and Nave, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated neurofilament light chain (NfL) is a more recently discovered biomarker of neurodegenerative diseases, including AD, frontotemporal dementia, amyotrophic lateral sclerosis, and multiple sclerosis (Chatterjee et al, ; Gille et al, ; Goossens et al, ; Siller et al, ). An increase in NfL in CSF and blood is interpreted as an indication of ongoing axonal damage (Lee, Taghian, & Petratos, ). Although both tau and NfL are both markers of neurodegeneration, they represent different degenerative processes in the brain.…”
Section: Effect Of Nb‐360 On Ad‐relevant Pathologies Downstream Of Aβmentioning
confidence: 99%